Moderating Effect of BMI on the Relationship Between Sympathetic Activation and Blood Pressure in Males with Obstructive Sleep Apnea - Chen B (Dove Medical Press, 2021)
Baixin Chen,1,2 Virend K Somers,3 Xiangdong Tang,4 Yun Li1,2 1Department of Sleep Medicine, Shantou University Mental Health Center, Shantou University Medical College, Shantou, People’s Republic of China; 2Sleep Medicine Center, Shantou University Medical College, Shantou, People’s Republic of China; 3Department of Cardiovascular Medicine, Mayo Clinic, Rochester, MN, USA; 4Sleep Medicine Center, Translational Neuroscience Center, West China Hospital, Sichuan University, Chengdu, People’s Republic of ChinaCorrespondence: Yun LiDepartment of Sleep Medicine, Shantou University Mental Health Center, Shantou University Medical College, Shantou, People’s Republic of ChinaEmail s_liyun@stu.edu.cnBackground: Sympathetic activation is a primary mechanism mediating increased blood pressure (BP) in obstructive sleep apnea (OSA). However, the relationships between overweight/obesity, sympathetic activation and BP in OSA are not well understood. We hypothesized that increased sympathetic drive is associated with increased BP in normal weight, but not in overweight/obese males with OSA. We therefore examined the effects of body mass index (BMI) on the association between sympathetic activation and BP in males with OSA.Methods: We studied 115 males with OSA recruited consecutively from clinic. Twenty-four-hour urinary norepinephrine was used to assess sympathetic activation. Blood pressure was measured both in the evening and in the morning. Hypertension was defined based on either BP measurements or an existing diagnosis. Linear and logistic regressions were conducted to examine the associations between sympathetic activation and both BP and risk of hypertension.Results: We found 24-hour urinary norepinephrine levels were associated with systolic and diastolic BP (SBP, β=0.157, p=0.082; DBP, β=0.212, p=0.023) and mean arterial pressure (MAP, β=0.198, p=0.032) after adjusting for confounders. Interestingly, these associations were modified by overweight/obesity. After adjusting for confounders, increased 24-hour urinary norepinephrine levels were significantly associated with elevated SBP (β=0.454, p=0.012), DBP (β=0.399, p=0.041), and MAP (β=0.432, p=0.023) in normal weight, but not in overweight/obese patients (all p> 0.2). Similar findings were observed in the associations between 24-hour urinary norepinephrine levels and hypertension.Conclusion: Sympathetic activation is associated with elevated BP in normal weight but not in overweight/obese males with OSA, suggesting that BMI may moderate the association between sympathetic activation and BP in males with OSA.Keywords: obesity, overweight, sympathetic activation, blood pressure, hypertension, obstructive sleep apnea